Políticas de avaliação em larga escala como ferramenta de gestão educacional - Lima, Jaqueline Bonfim de Souza (2020)
Neoliberal policies from the 1990s guided the reform of the Brazilian State, redefining its role, which ceased to be directly responsible for the implementation of public policies, and began to act as regulator and evaluator. In this context, in the field of education, large-scale assessments, as a management tool, have been intensified in the public basic education networks. Therefore, the objective of this research was to analyze the extent to which the Large-scale Assessment materializes the assumptions of management administration and, thus, translates the perspective of quality and social control that characterize the evaluating / regulating State. From this objective, in the first chapter, we present some considerations regarding the reform of Educational Management. In the second chapter, initially, we will approach Large-scale Assessment in the context of State reform and the adoption of the managerial public administration model and the New Public Management, focusing on the categories of quality and social control. Subsequently, based on documents from the National Institute for Educational Studies and Research Anísio Teixeira and the National Fund for the Development of Education, we seek to understand Evaluation as a Management tool and the materialization of the assumptions of Management Administration that began in 1995, translating the perspective of quality and social control that characterize the evaluating / regulating State. In the final considerations, we seek to resume the path of the analyzes developed in the work, seeking to rescue the issues defined a priori, and within the limits of this work, contribute qualitatively to the discussions regarding the Evaluation on a large scale. We identified in the documents analyzed in this research, that the use of the results of external evaluations as an instrument of Educational Management, has guided educational policy, teaching and student learning, as well as strategies for teacher education, promoting ranking and competition between schools by disseminating the indexes. The documents also help us to identify how this evaluation policy has fostered teachers' resource allocation and salary incentive policies.